2024
DOI: 10.1021/jacs.4c04496
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Addition of (Hetero)aryl (Pseudo)halides at Palladium(0): Origin and Significance of Divergent Mechanisms

Matthew J. Kania,
Albert Reyes,
Sharon R. Neufeldt

Abstract: Two limiting mechanisms are possible for oxidative addition of (hetero)aryl (pseudo)halides at Pd(0): a 3-centered concerted and a nucleophilic displacement mechanism. Until now, there has been little understanding about when each mechanism is relevant. Prior investigations to distinguish between these pathways were limited to a few specific combinations of the substrate and ligand. Here, we computationally evaluated over 180 transition structures for oxidative addition in order to determine mechanistic trends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…To assess this hypothesis, we have conducted a combined computational and experimental study of the oxidative addition rate and site selectivity for substituted halopyridines to L 2 Pd(0), using Pd(PCy 3 ) 2 as an exemplar . In a concurrent and complementary study, Neufeldt and co-workers further establish the interplay between Pd speciation, ligand identity, and orbital symmetry in determining the mechanism of oxidative addition for unsubstituted phenyl–X and pyridyl–X substrates (X = F, Cl, Br, I, OTf) …”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…To assess this hypothesis, we have conducted a combined computational and experimental study of the oxidative addition rate and site selectivity for substituted halopyridines to L 2 Pd(0), using Pd(PCy 3 ) 2 as an exemplar . In a concurrent and complementary study, Neufeldt and co-workers further establish the interplay between Pd speciation, ligand identity, and orbital symmetry in determining the mechanism of oxidative addition for unsubstituted phenyl–X and pyridyl–X substrates (X = F, Cl, Br, I, OTf) …”
Section: Resultsmentioning
confidence: 95%
“…Hartwig’s group and Baird’s group have independently shown via kinetic analysis that both Pd(PCy 3 ) n ( n = 1, 2) species are kinetically relevant for Ph–Cl and Ph–Br OA. Neufeldt’s group has also shown that 12- and 14-electron Pd(0) species undergo different OA mechanisms depending on the substrate. , Further work is underway to improve the scope and accuracy of our oxidative addition models by expanding our data sets to better represent both FMO-based effects with a variety of substitution patterns and Pd(0) speciation with a variety of phosphine ligands.…”
Section: Resultsmentioning
confidence: 99%